Clinical Holistic Medicine: Tools for a Medical Science Based on Consciousness - Søren Ventegodt; Mohammed Morad; Niels Jorgen Andersen; Joav Merrick (The Scientific World Journal)
Biomedicine focuses on the biochemistry of the body, while consciousness-based medicine — holistic medicine — focuses on the individual's experiences and conscious whole (Greek: holos, whole). Biomedicine perceives diseases as mechanical errors at the micro level, while consciousness-based medicine perceives diseases as disturbances in attitudes, perceptions, and experiences at the macro level — in the organism as a whole. Thus, consciousness-based medicine is based on the whole individual, while biomedicine is based on its smallest parts, the molecules. These two completely different points of departure make the two forms of medicine very different; they represent two different mind sets and two different frames of reference or medical paradigms. This paper explains the basic tools of clinical holistic medicine based on the life mission theory and holistic process theory, with examples of holistic healing from the holistic medical clinic.